Intrinsic Motivation, Emotional Intelligence, and Perceived Organizational Citizenship Behavior among Employees in Service Organizations - Pramanik, Sugandha; Chatterjee, Ishita (Prabandhan: Indian Journal of Management, 2015)
This study investigated the relationship between intrinsic motivation, emotional intelligence, and organizational citizenship behavior of various service sector organizations ; 248 employees were selected from 35 service sector organizations (public and private) in and around Kolkata. The following tools were administered to test the hypotheses: (a) Intrinsic and Extrinsic Motivation: What Do You Look For In A Job? by Pareek (1997); (b) Emotional Intelligence Scale by Chaddha and Singh (Singh, 2003); (c) Organizational Citizenship Behavior Checklist by Fox, Spector, Goh, Bruursema, and Kessler (2012). For analysis of the data, descriptive statistics, ANOVA, correlation and regression were used. The findings revealed that significant and positive relation existed between intrinsic motivation, emotional intelligence, and organizational citizenship behavior. Intrinsic motivation and emotional intelligence together predicted 27% of the total variance of organizational citizenship behavior. Intrinsic motivation and organizational citizenship behavior were found to be better in case of private-sector employees than in case of public-sector employees. As it was found that intrinsic motivation and emotional intelligence are positively related to organizational citizenship behavior, so employers may motivate their employees intrinsically to retain them and while hiring, employers may consider candidates with high emotional intelligence who can benefit the organization.